ANALYSIS OF SOCIOLOGY AND CHARACTER EDUCATIONAL VALUES IN NOVEL OF BUNDA LISA - Abdul Rahim (LPPM Universitas Samawa, 2018)
This research aimed to describe the element of sociology and educational values in novel of Bunda Lisa written by Jombang Santani Khairen. This research was qualitative descriptive. The source of data was from novel of Bunda Lisa work of Jombang Santani Khairen. The technique of data collection were critically reading and noting. To test the validity of data, the writer used triangulation theory. Technique to analysis data used interactive analysis technique that consist of: data reduction, data display and drawing conclusion. Result of the research showed that there were six of social problem namely: 1) lack of community awareness toward education. 2) dissatisfaction of community, 3) economic crisis, 4) the lack of government facility, 5) poverty, and 6) lack of job opportunity. While the character educational value in novel of Bunda Lisa were: (1) religion values, (2) tolerance, (3) hard work, (4) curiosity, (5) social awareness, (6) environmental awareness, and (7) creative.